Pengaruh Pengalaman Kerja dan Pelatihan terhadap Produktivitas Kerja Pegawai PDAM Kota Solok - Mardhatila Fitri Sopali; Chintya Ones Charli; Ai Elis Karlinda; Putri Azizi (Universitas Batanghari, 2023)
This study aims to determine: (1) The positive and significant effect of Work Experience on Work Competence (2) The positive and significant effect of Training on Work Competence. (3) Positive and significant influence between Work Experience on Work Productivity (4) Positive and significant influence between Training on Employee Work Productivity. (5) The positive and significant effect of work productivity on work competence. This study uses quantitative research where the population in this study are employees of PDAM Solok city. The sample in this study were 51 people. Sampling using accidental sampling technique, while data collection was done using a questionnaire. Testing the instrument using validity and reliability tests. Data analysis used multiple linear regression test, t test and F test and determination test. The result of this research is Work Experience is able to mediate Work Productivity on Work Competence. Training is able to mediate Work Productivity on Work Competence.